(untitled) (Research, Society and Development, 2021)
The kombucha tea is a beverage resulting from the fermentation of sweetened green and/or black tea and added to a culture containing a symbiotic consortium of bacteria and yeasts, thus presenting an antimicrobial and antioxidant character. The fermentation of kombucha tea takes place at room temperature, over a period of 3 to 60 days. At the end of fermentation, the beverage is a cocktail of chemical components, organic acids, fiber, and ethanol. Studies show that the regular consumption of the beverage prevents several diseases, strengthening the immune system, benefits which are related to the presence of polyphenols, gluconic acid, amino acids, antibiotics, among other micronutrients generated during fermentation. Therefore, the present work aimed at producing kombucha tea using green tea as a substrate on a laboratory scale, evaluating the physicochemical properties, bioactive compounds and antioxidant activity of kombucha tea in order to characterize it. The analyses performed were pH, total soluble solids (TSS), titratable acidity (TA), ratio (TSS/TA), coloration in the parameters (L*, a* and b*), antioxidants DPPH, ABTS and polyphenols. From the results obtained, in its physical-chemical characterization, it was observed a decrease in the pH and SST value due to the presence of organic acids and sucrose used as a fermentative substrate. Furthermore, the results of bioactive compounds and antioxidant activity are related to the extraction of compounds from green tea under the conditions used on a laboratory scale, and that the resulting beverage presented characteristics similar to those evaluated by other authors. Therefore, this study encourages scientific research on this beverage, kombucha is still mainly produced through natural fermentation processes, and therefore uncontrolled.